A novel soluble phthalocyanine capable of binding four boronic esters - Ozcelik, Sennur; Karaoglan, Gulnur Keser; Gumrukcu, Gulsah; Gul, Ahmet (Tubitak Scientific & Technological Research Council Turkey, 2012)
A novel Zn phthalocyanine bearing 4 salicylideniminophenyloxy substituents on peripheral positions was synthesized from the reaction of 4-aminophenoxy substituted phthalocyanine and salicylaldehyde. The condensation reaction of salicylidene Schiff base groups and benzeneboronic acid produced a new phthalocyanine carrying benzeneboronic acid ester derivatives as substituents. Ethoxy groups were bound to boronic acid as a second ligand. The presence of B-N bond interactions enhanced the stability of this boronated phthalocyanine derivative, which exhibited sufficient air stability during the purification and characterization processes. The novel compounds were characterized by using elemental analysis, IR, H-1-NMR, B-11-NMR, C-13-NMR, UV-Vis and MALDI-TOF MS spectral data.
Keywords: Phthalocyanine Schiff base; zinc; boronate complex; benzeneboronic acid; B-11-NMR; 3-AMINOPHENYLBORONIC ACID; ORGANOBORON COMPOUNDS; MACROCYCLES; SUBSTITUENTS; DERIVATIVES; COMPLEXES; BEARING; BULKY; ANHYDRIDE; POLYMERS; Chemistry; Engineering